A Recent Advancement: Casing while Drilling – A Viable Alternative to Conventional Drilling - Foidas, Ion; Stefanescu, Dan-Paul; Serbancea, Mihai (Recent Developments in Engineering Research Vol. 12, 2021)
Mankind’s increased requirement for and dependence on energy resources, including the resources resulting from discovery and development of new hydrocarbon commercial reservoirs involves the use of new technologies such as optimization of the drilling process by reducing the non-productive time, the costs and the risks. Casing while drilling involves elimination of classical drilling string by using the casing string both for transmission to the bit of the mechanical energy and for circulation of drilling fluid into the well. Casing while drilling, constantly improving over time, has proven an efficient method to reduce risks, especially those related to the presence of a conventional drill string in the borehole, maintenance of borehole stability or loss of circulation. Although there is a number of technical or perception barriers related to the use of casing drilling, the important benefits of this technology related to reduced drilling time and problems associated to the drilling string make it an increasingly viable alternative to conventional drilling. The experience in applying this technology has proven that it can reduce the time of well execution and sometimes it lowers the costs in relation to drilling depth.